Performance and problems of the housing sphere in Russia - Dmitrieva Ekaterina (MATEC Web of Conferences, 2018)
Systematization of risks in the field of housing-and-communal services and recommendations on the neutralization of problem zones were offered. The objective is the diagnostics of the situation in the sphere of housing-and-communal services and the identification of risk zones. The author concludes that the information on risk factors is necessary for the creation of the system of risk prevention, and assumes further development of the measures for the effective management in this sector.